Model Tingkat Kemiskinan di Kabupaten/Kota Provinsi Riau: Menggunakan Regresi Data Panel - Rahmadeni Rahmadeni; Nurjannah Nurjannah (KUBIK, 2021)
The purpose of this study is to model the poverty rate in the districts/cities of Riau province in 2015-2019. In this study, the panel data regression method was used to model the poverty level in the districts/cities of Riau province. There are three approaches to predict panel data regression, those are the common effect model (CEM), the  fixed effect model (FEM), and the random effect model (REM). The test results show that the problem of poverty levels in the districts/cities of Riau province in 2015-2019 is more accurately modeled with the fixed effect model (FEM) approach. From the FEM model formed, the effect of the poverty rate in the district/city of Riau province is caused by the average length of schooling of 12.136671 and economic growth of 0.304306 with the coefficient of determination (Adjusted R-square) reaching 98.62%.